2008
DOI: 10.1093/bja/aem400
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative tobacco use interventions in Japan: a survey of thoracic surgeons and anaesthesiologists

Abstract: Although current rates of intervention provided by anaesthesiologists and surgeons are low, there is considerable interest among these physicians in learning more about interventions. Given the relatively high prevalence of smoking in Japan and the potential for surgery to serve as a 'teachable moment' to promote abstinence from smoking, leadership by these specialists in the area of tobacco control could have a major impact on public health in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 23 publications
(21 reference statements)
1
44
0
Order By: Relevance
“…Initiation of smoking cessation was visible in 15.3% of our OCRs, which is a strikingly low number, considering that previous studies have found 58 to 70% of surgeons to advise their patients to quit smoking before surgery [13][14][15][16]. Insufficient training, lack of knowledge, lack of perceived efficacious interventions, and lack of time have proven the most significant smoking cessation barriers for surgeons [13,16,17].…”
Section: Discussionmentioning
confidence: 84%
“…Initiation of smoking cessation was visible in 15.3% of our OCRs, which is a strikingly low number, considering that previous studies have found 58 to 70% of surgeons to advise their patients to quit smoking before surgery [13][14][15][16]. Insufficient training, lack of knowledge, lack of perceived efficacious interventions, and lack of time have proven the most significant smoking cessation barriers for surgeons [13,16,17].…”
Section: Discussionmentioning
confidence: 84%
“…Second, Chinese anesthesiologists recognize their responsibilities and are willing to engage in tobacco control efforts. For example, the perception of responsibility to make sure that patients get help in quitting is much stronger among Chinese anesthesiologists compared with their American and Japanese counterparts (71% agreed or strongly agreed with this item, compared with 20 and 35%, respectively, in the prior surveys 17,18 ). They also have a strong interest in learning about ways to help patients quit, including participation in educational programs and other training opportunities.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with previous studies of physicians, nonsmoking anesthesiologists were more likely to advise patients about the health risks of smoking and advise smokers to quit. 15,16,18 This funding suggests that efforts to help anesthesiologists quit smoking may increase the frequency with which these physicians provide tobacco interventions. Most anesthesiologists who smoked were interested in quitting and many of them had made quit attempts in the past year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations